Protecting tropical forests from the rapid expansion of rubber using carbon payments - Eleanor M. Warren-Thomas (Nature Portfolio, 2018)
Expansion of rubber plantations threatens tropical forest carbon stocks and biodiversity, but may be dis-incentivised using carbon finance. Here, Warren-Thomas et al. use forest and agricultural data for Cambodia to show that carbon prices of $30–$51 per tCO2 are needed to match forest protection costs.